Structural properties of particle deposits at heterogeneous surfaces. (23rd June 2015) - Stojiljković, D; Šćepanović, J R; Vrhovac, S B; Švrakić, N M
Abstract: The random sequential adsorption (RSA) approach is used to analyze adsorption of spherical particles of a fixed radius on nonuniform flat surfaces covered by rectangular cells. The configuration of the cells (heterogeneities) was produced by performing RSA simulations to a prescribed coverage fraction . Adsorption was assumed to occur if the particle (projected) center lies within a rectangular cell area, i.e. if sphere touches the cells. The jammed-state properties of the model were studied for different values of cell size α (comparable with the adsorbing particle size) and density . Numerical simulations were carried out to investigate adsorption kinetics, jamming coverage, and structure of coverings. Structural properties of the jammed-state coverings were analyzed in terms of the radial distribution function g ( r ) and distribution of the Delaunay 'free' volumes P ( v ). It was demonstrated that adsorption kinetics and the jamming coverage decreased significantly, at a fixed density, when the cell size α increased. The predictions following from our calculation suggest that the porosity (pore volumes) of deposited monolayer can be controlled by the size and shape of landing cells, and by anisotropy of the cell deposition procedure.